A crise e as novas fronteiras para a indústria fonográfica - Lannes, Wilson Vieira (2009)
The world's record industry has been undergoing a deep crisis over the past years, and has been seeking ways to overcome the fall in legal CD and DVD sales. Paradoxally, consumption of music in its varied forms has been increasing over the same period. Within this adverse scenario, record companies have been trying to adjust their business models so as to encompass other products and services bearing a direct relationship with music. This paper aims at identifying the causes as well as assessing opportunities and initiatives within the market aiming at allowing the record industry to overcome the ongoing crisis. The objective of this paper is to provide an assessment of the current situation and propose alternatives to overcome the crisis, including digital music and the market of concerts and events as potential opportunities for the industry.